Analisis Rasio Solvabilitas Dan Rasio Profitabilitas Dalam Menilai Kinerja Keuangan Pada Perum BULOG Kanwil Sumsel Dan Babel Periode 2018 – 2020 - Sri Sutandi; Sari Mustika Widyastuti; Resty Dasryanti Nadhilah; Lia Sari; Dimas Try Handoko (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2022)
The purpose of this study was to examine the results of the financial performance of Perum BULOG, the Regional Office of South Sumatra and Babylon in 2018- 2020. The data analysis technique used solvency analysis (debt to assets and debt to equity) and profitability ratios (return on assets and net profit margin) based on financial reports at Perum BULOG, South Sumatra and Babel Regional Offices for 2018-2020. This research was conducted at Perum BULOG Regional Office of South Sumatra and Babylon. The data used secondary data in the form of documents consisting of company history, company vision and mission, company values, organizational structure and financial reports at Perum BULOG, South Sumatra and Babel Regional Offices. The results of this study indicated that, the solvency ratio analysis calculated using the debt to asset ratio had a financial performance in poor condition; the company had a total debt that was greater than the total assets. It meant that the company had not been able to cover its debts with its assets. If calculated using the debt to equity ratio, the financial performance was in poor condition, meaning that the company was not able to utilize equity in financing the company's debt. The results of the analysis with the profitability ratios calculated using the return on asset ratio and the net profit margin ratio at Perum BULOG, the South Sumatra and Babel Regional Offices, were in poor condition, because the profits generated by the company each year decrease and the company had not been able to increase profits, this showed financial performance the company was not good.